The Centralization of Australian Federalism 1901–2010: Measurement and Interpretation. Issue 1 (27th November 2018) - Fenna, Alan
Abstract: As part of a larger comparative project, "Dynamic De/Centralization in Federations, " this article studies the dynamics of Australian federalism since 1901. A constitution drafted in the 1890s left the majority of domestic governance responsibilities to the States. Within two decades, though, a process, continuing to this day, was underway whereby the financial power and the policy reach of the Commonwealth expanded in an apparently inexorable and irreversible fashion. This article charts those developments across both a broad sweep of policy domains and in respect of changing fiscal relations for the Australian case and attempts to provide a more systematic assessment of the extent, degree, and timing of change since Federation than previously attempted. It then relates the main patterns of change, over time and across policy domains, to the apparent mechanisms and, in turn, to a range of hypothesized causes.